Analisis KUD Cilongok Menggunakan Space Matrix Strategi Pengembangan Unit Simpan Pinjam dan UKM Mart - Mukarromah, Laili; Ulfi, Lie Aulia; Melani, Niken; Shafrani, Yoiz Shofwa (FEB Universitas Maritim Semarang, 2025)
This research aims to analyze the strategic position of the Village Unit Cooperative (KUD) Cilongok using the Strategic Position and Action Evaluation (SPACE) Matrix method and formulate development strategies for savings and loan units and supermarket businesses. The research method uses a quantitative-qualitative approach with data collection techniques through observation, interviews, and documentation. SPACE Matrix analysis is carried out by identifying factors of financial strength, competitive advantage, industry strength, and environmental stability. The results show that KUD Cilongok is in an aggressive quadrant position with relatively high values of financial strength and industry strength. The recommended strategies include market penetration, market development, product development, and business diversification. The implementation of these strategies is expected to improve the performance of KUD Cilongok's savings and loan units and supermarket businesses, as well as improve the welfare of members and the surrounding community.